Lambda-Based Prioritisation In Multichannel Optical Ip Network - Yahya, Wan Salman (2003)
The explosion of the Internet and its application creates demand for more network resources and bandwidth. The internet traffics such as voice, video and interactive applications are more susceptible to delay and jitter while bursty data traffic such as e-mail and file transfer are more sensitive to loss. To accommodate the bandwidth demands, the trend of the network also experiences a major change from copper-based to optical fibre transmission link. Besides of its many superior properties, optical fibre has an extraordinary limitless bandwidth. However increasing the bandwidth in respond to the need of bandwidth demands is not necessarily an appropriate solution. As more and more applications use the bandwidth, congestion still occurs. Therefore, the Quality of Service (QoS) is introduced into the network. Different type of Internet traffic requires different treatment while propagating along the network and thus requires a specific QoS characteristic.In this research, the traffic is split into four levels of priority classes that require different levels of QoS treatment. Each class of traffic is transmitted at different wavelength (A). The highest priority class deserved the best QoS treatment while lower prichity classes needs the lower QoS treatment. Therefore, there are four channels to carr four types of traffic. The Sub-Carrier Modulation (SCM) technique is used to cal the optical traffic and it is transmitted on to the optical communication ink using Wavelength Division Multiplexing (WDM) technology. The Fib( Delay Line (FDL) that acts as an optical buffer is used to resolve the contention on the input port at the receiver. During the contention resolution, the lower priority traffic is buffered while transmitting the higher priority traffic. The simulation results show that the highest priority traffic gets the best treatment while propagating in the network. The performance of the highest priority traffic is the best whereby it has low loss, low delay and yet high throughput and efficiency. The lower priority traffic sustains high loss, longer delay but low throughput and efficiency.